Low-temperature behavior of disordered magnetic impurities: Distribution of effective Kondo temperatures - Zvyagin, A.A.; Makarova, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Several rare-earth compounds, low-dimensional organic conductors, and spin chains exhibit low-temperature divergences of their magnetic susceptibility and specific heat (non-Fermi-liquid behavior). Such divergences are often related to disordered ensembles of magnetic impurities in those systems. In this work the distribution function of the effective characteristic of a single magnetic impurity, the Kondo temperature, is derived. We calculate how distributions of Kondo temperatures depend on the effective dimensionality of the problem and on the concentration of impurities.